2021
DOI: 10.3390/app11209668
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Intertwined Relationships of the Drivers for University Technology Transfer

Abstract: Universities are the best places to gather knowledge and innovation, but the basis of technological development lies in talented R&D personnel who provide services to enterprise R&D activities, research institutions, and universities. Universities also gather many elites who cultivate talent for the country. However, universities do not have adequate technology transfer experience and do not network in industrial circles, which results in a huge gap between the concept and the practical result. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 106 publications
(149 reference statements)
0
5
0
Order By: Relevance
“…There are two ways to express interval grey numbers, one being the conventional data range expression (see the data on the left of each column in the table) and the other being the combination expression of a kernel and the degree of greyness (see the data on the right of each column in the table). [15,20] 17.5 0.25 [9,10] 9.5 0.08 [4,6] 5.0 0.33 [22,30] 26.0 0.13 [10,15] 12.5 0.17 S 2 [20,22] 21.0 0.10 [12,14] 13.0 0.15 [4,7] 5.5 0.50 [30,35] 32.5 0.08 [25,32] 28.5 0.24 S 3 [16,30] 23.0 0.70 [11,13] 12.0 0.15 [5,8] 6.5 0.50 [40,50] 45.0 0.17 [18,28] 23.0 0.34 S 4 [25,30] 27.5 0.25 [13,18] 15.5 0.38 [7,9] 8.0 0.33 [60,65] 62.5 0.08 [20,35] 27.5 0.52 S 5 [22,24] 23.0 0.10 [10, 13] 11.5 0.23 [4,6] 5.0 0.33 [45,50] 47.5 0.08 …”
Section: Basic Data and Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…There are two ways to express interval grey numbers, one being the conventional data range expression (see the data on the left of each column in the table) and the other being the combination expression of a kernel and the degree of greyness (see the data on the right of each column in the table). [15,20] 17.5 0.25 [9,10] 9.5 0.08 [4,6] 5.0 0.33 [22,30] 26.0 0.13 [10,15] 12.5 0.17 S 2 [20,22] 21.0 0.10 [12,14] 13.0 0.15 [4,7] 5.5 0.50 [30,35] 32.5 0.08 [25,32] 28.5 0.24 S 3 [16,30] 23.0 0.70 [11,13] 12.0 0.15 [5,8] 6.5 0.50 [40,50] 45.0 0.17 [18,28] 23.0 0.34 S 4 [25,30] 27.5 0.25 [13,18] 15.5 0.38 [7,9] 8.0 0.33 [60,65] 62.5 0.08 [20,35] 27.5 0.52 S 5 [22,24] 23.0 0.10 [10, 13] 11.5 0.23 [4,6] 5.0 0.33 [45,50] 47.5 0.08 …”
Section: Basic Data and Results Analysismentioning
confidence: 99%
“…High-tech companies are exposed to eight dimensions of risk, including technology risk, capital risk, patent risk, talent risk, management risk, policy risk, industry risk and market risk, while achieving high returns through technological innovation [7]. Universities, although they gather many elites and train talents for the country, do not have enough experience in technology transfer or networks in industry and should focus on technology transfer activities, whose technology market applicability, attitude and ability of talents are key factors [8]. In enhancing corporate innovation, attention should be paid to macro regulation and supervision of green technologies, optimization of environmental management, strengthening of incentives for green innovation talents and strengthening of green technology R&D and service centers [9].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time at the level of individual researchers, Audretsch et al (2006) found the negative influence of citations on scientific commercialization. Sun (2021) highlights the importance of the attitude and ability of top university management in achieving good R&D results. Other papers also mention such factors as university-industry cooperation, flexible management systems, and national promotion of entrepreneurial behavior in general (Carayannis et al 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the one hand, some of the influencing factors are internal to the university, such as the lack of well-trained staff and inventions processing capacity [ 12 ], insufficient rewards for faculty involvement in UTT [ 32 ], university’s academic eminence [ 33 ], medical schools [ 34 ] and science parks [ 35 ]. Sun [ 36 ] used the DEMATEL information analysis method to discuss the key UTT internal factors, with results showing that the effect of different factors on UTT widely varied. Institutions and infrastructure are supportive of increasing university patents [ 37 , 38 ].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%